MULTICOLOR PHOTOMETRY OF LONG PERIOD VARIABLES - MENDOZA, EUGENIO (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1967)
Multicolor photometry is made of sixty seven late type stars over wavelengths ranging from 0.3µ to 10.2µ. The observations enable one to distinguish between classes M, S and C. The M and S stars unreddened by interstellar extinction can be separated and t
BOL OBS TONAN TACUB
Keywords: MULTICOLOR, PHOTOMETRY, LONG PERIOD, VARIABLES; ASTRONOMIA Y ASTROFISICA; ASTRONOMIA OPTICA; FOTOMETRIA